Sample‐size estimation is not reported in 24% of randomised controlled trials of inflammatory bowel disease: A systematic review. Issue 1 (18th February 2021) - Iheozor‐Ejiofor, Zipporah; Lakunina, Svetlana; Gordon, Morris; Akintelure, Daniel; Sinopoulou, Vasiliki; Akobeng, Anthony
Abstract: Background: Sample‐size estimation is an important factor in designing a clinical trial. A recent study found that 65% of Cochrane systematic reviews had imprecise results. Objective: This study set out to review the whole body of inflammatory bowel disease (IBD) randomised controlled trials systematically in order to identify the reporting of sample‐size estimation. Methods: We conducted a comprehensive hand search of the Cochrane Library and Cochrane IBD Specialized Trials Register. We extracted information on relevant features and the results of the included studies. We produced descriptive statistics for our results. Results: A total of 242 randomised controlled trials were included from 44 Cochrane systematic reviews. About 25% of the studies failed to report on sample‐size estimation. Of those that did report on sample‐size estimation, 33% failed to recruit their target sample size. Conclusions: Around half of the randomised controlled trials in IBD either do not report sample‐size estimation or reach their recruitment target with the level of detail in reporting being limited.